Electron pitch angle/energy distribution in the magnetotail. Issue 9 (10th September 2014) - Artemyev, A. V.; Walsh, A. P.; Petrukovich, A. A.; Baumjohann, W.; Nakamura, R.; Fazakerley, A. N.
Abstract In this paper we utilize 9 years of Cluster observations in the Earth's magnetotail to investigate electron pitch angle/energy distributions. We mainly concentrate on the population of anisotropic electrons with a dominance of the parallel phase space density and energies larger than 100 eV. The energy distribution of this population strongly varies with the downtail distance (the near‐Earth x>−12RE and the tail x∈[−20, −12]RE) and along the dawn‐dusk direction (the midnight |y|<10RE and the flanks |y|>10RE). In the tail‐midnight domain the electron anisotropic population is present at all energy ranges up to 20 keV, while at the tail‐flank domain only the energy range below several keV is filled by this population. In the near‐Earth domain the only anisotropic electrons are cold, with energies less than 1 keV. We investigate the dependence of the energy distribution of the anisotropic electron population on the system parameters for the midnight‐tail domain where the main statistics is collected. The increase of the Bz GSM component of the magnetic field corresponds to an increasing energy range filled by anisotropic electrons. The increase of the electron temperature anisotropy is provided by the enhancement of the anisotropic population at all energies up to 20 keV. There is no distinct dependence of the electron anisotropic population on the plasma flow velocity. The increase of the electron temperature corresponds to shifting of the electron anisotropic population toward higher energies. We propose a simple model of the pitch angle/energy distribution of this electron population and discuss the origin of anisotropic electrons in the magnetotail.